MERLOT bookmark collections [electronic resource] - California State University System; MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 2017)
Quoted from the homepage: MERLOT users often find learning materials in the collection that they wish to collect and organize under a specific theme, topic, or label. Bookmark Collections help personalize the MERLOT collection for members. It is a compilation of online resources from MERLOT that MERLOT Members can access easily to use for specific purposes, classes or topics. The owner of the Bookmark Collection can annotate each collection to more easily explain the purpose of it. A Bookmark Collection, for example, can be used to save a set of learning materials related to a topic in a course. They are discoverable and shareable by other MERLOT users. The frequency with which a material is stored in a Bookmark Collection is considered to be a ?statement? of the popularity or value of that material. For this reason, MERLOT displays the number of Bookmark Collections in which each material has been placed.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Aids and devices -- Open educational resources. .; Education, Higher -- Aids and devices -- Open educational resources. .